If I never forever endeavor - Meade, Holly (Somerville, Mass. : Candlewick Press, 2011)
A young bird sits inside his cozy nest worrying if he is ready to try out his wings and fly.
Booklist starred
Publisher's Weekly
Wilson's Children
Booklist starred, April 2011
Horn Book, October 2011
Kirkus Starred, March 2011
Keywords: Birds -- Infancy -- Juvenile fiction; Courage -- Juvenile fiction; Flight -- Juvenile fiction; Animals -- Infancy -- Fiction; Birds -- Fiction; Courage -- Fiction; Flight -- Fiction; Stories in rhyme; Animal babies -- Fiction; Birds -- Fiction; Courage -- Fiction; Flight -- Fiction; Stories in rhyme; Picture books for children